The Effect of Pop-Up Book Usage on the Reading Comprehension Achievement of the Fifth Graders at SDN Bakungan in Academic Year 2023/2024 - Eva Maharani; Yuli Sugianto; Ahmad Irsyadul Anam; Feby Regita Cahyani (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2026)
This study aimed to determine whether the use of pop-up books affects the reading comprehension achievement of fifth-grade students at SDN Bakungan in the 2023–2024 academic year. A quantitative approach with a one-group pretest–posttest design was employed. The sample consisted of 21 students from class VA, and data were collected using a reading comprehension test. The results showed an improvement in students’ performance, with the mean pretest score of 66.67 increasing to 87.14 in the posttest. Statistical analysis using the Wilcoxon test yielded a significance value of 0.001, which is lower than 0.05, indicating a significant effect of pop-up book usage on students’ reading comprehension. These findings suggest that pop-up books can serve as an effective and engaging instructional medium to enhance reading comprehension among elementary school students. Therefore, teachers are encouraged to integrate interactive media such as pop-up books into reading instruction, and future researchers may explore its application across different grade levels or in comparison with other instructional media.